Pendampingan UKM Batik Bakaran dalam Upaya Peningkatan Produktivitas dan Kualitas - Sugito Sugito; Alan Prahutama; Arief Rachman Hakim (Universitas Muhammadiyah Semarang, 2022)
The Covid-19 pandemic has greatly impacted the business sector, especially MSMEs (Micro, Small and Medium Enterprises). One of the government's efforts to overcome economic difficulties for affected MSME actors is capital assistance. In addition, MSMEs need assistance so that their managed businesses can run well in the midst of the COVID-19 pandemic. Diponegoro University through its community service program provides assistance to MSMEs. MSMEs that become partners are the SME Batik burned by Yuliati Warno and the SME Batik burned by Yahyu. Burnt batik is a typical batik of Pati district, Central Java. The method of implementing this activity is by analyzing the problems of SMEs through interviews and field observations. The program of activities carried out is based on the analysis of the problems that have been carried out. The program of activities includes aspects of production, aspects of licensing, aspects of marketing and aspects of human resources. Assistance is carried out by empowering SMEs including the use of appropriate technology, for example the use of feeders for the coloring and drying process, product diversification in the form of batik cloth masks. Licensing aspects include product standardization, such as the management of SIUP, registration of trademarks and processing of the